Divergent Total Syntheses of (−)‐Daphnilongeranin B and (−)‐Daphenylline. (5th December 2017) - Chen, Xiaoming; Zhang, Hai‐Jun; Yang, Xinkan; Lv, Houqiang; Shao, Xiaoru; Tao, Cheng; Wang, Huifei; Cheng, Bin; Li, Yun; Guo, Jingjing; Zhang, Jing; Zhai, Hongbin
Abstract: (−)‐Daphnilongeranin B and (−)‐daphenylline are two hexacyclic Daphniphyllum alkaloids, each containing a complex cagelike backbone. Described herein are the first asymmetric total synthesis of (−)‐daphnilongeranin B and a bioinspired synthesis of (−)‐daphenylline with an unusual E ring embedded in a cagelike framework. The key features include an intermolecular [3+2] cycloaddition, a late‐stage aldol cyclization to install the F ring of daphnilongeranin B, and a bioinspired cationic rearrangement leading to the tetrasubstituted benzene ring of daphenylline.